Effect of motor control training on muscle size and football games missed from injury - Hides, J. A.; Stanton, W. R.; Mendis, M. D.; Gildea, J.; Sexton, M. (Medicine & Science in Sports & Exercise, 2012)
Purpose: This panel-randomized intervention trial was designed to examine the effect of a motor control training program for elite Australian Football League players with and without low back pain (LBP).